Regulatory Dilemma and Innovation: A Critical Analysis of Business Law in Indonesia Facing Technological Disruption - Purborini, Vivi Sylvia; Suryaningsih (Ilomata International Journal of Social Science, 2025)
This study critically examines the regulatory challenges facing Indonesian business law amid rapid technological disruption, using normative legal research with a doctrinal approach. Analyzing legislation, legal principles, and academic literature, it identifies a persistent tension between legal certainty and the imperative to innovate. Indonesia’s regulatory framework often trails digital transformation and global integration, producing delays that generate uncertainty for firms, weaken consumer protection, and heighten risks of unfair practices. The literature remains thin on the dynamic mismatch between evolving business models and regulatory responses, underscoring the need for studies that integrate empirical evidence with theory to inform adaptive rule-making. Cross-border transactions compound complexity, as jurisdictional overlaps constrain national authorities in cases involving transnational actors; these pressures are systemic, bearing directly on the effectiveness, legitimacy, and competitiveness of Indonesian business law. Rather than reacting after the fact, business law should act as a driver of responsible innovation—promoting growth while respecting Indonesian legal and cultural values and protecting the public interest. This requires a normative framework attentive to local socio-cultural specificities, distinct from dominant Western accounts of responsible innovation. Indonesia’s capacity to navigate disruption thus depends not only on legislative reform but also on a responsive, collaborative, and inclusive legal ecosystem that is anticipatory, integrative, and resilient. The study contributes theoretically by clarifying how to design institutions that deliver legal certainty while enabling sustainable innovation, and practically by offering a foundation for policymakers to build a fair, competitive, future-ready regime.